(untitled) (Perner’s Contacts, 2014)
This article is dedicated to the issue of project finance as a tool for specific loan financing of capital intensive infrastructure projects. It describes the project finance in terms of its key aspects. Introduction contains a definition of project finance, project finance classification in terms of the possibility of recourse (sanction) by the creditor, identification and characteristic of groups of entities involved in project finance. The next section defines the preparatory phase, implementation phase and final phase of the project finance process. This section is dedicated to the definition of possible ways of loan guarantee and identification of common features of project finance structures, which can be considered simultaneously for the benefits. In conclusion are briefly defined the project criteria that determine his eligibility for the application of this financing instrument.